2017
DOI: 10.1103/physrevmaterials.1.032001
|View full text |Cite
|
Sign up to set email alerts
|

Rb2Ti2O5 : Superionic conductor with colossal dielectric constant

Abstract: Electrical conductivity and high dielectric constant are in principle self-excluding, which makes the terms insulator and dielectric usually synonymous. This is certainly true when the electrical carriers are electrons, but not necessarily in a material where ions are extremely mobile, electronic conduction is negligible and the charge transfer at the interface is immaterial. Here we demonstrate in a perovskite-derived structure containing five-coordinated Ti atoms, a colossal dielectric constant (up to 10 9 )… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 37 publications
4
26
1
Order By: Relevance
“…In this case, ions are not accumulated and there is no building up of charge at the interface. This is in contradiction to what is observed in the present system where ions remain accumulated, a giant polarization (of the order of 0.1 C cm −2 ) is created 14 , and where no particular gas production is observed at the anode. Moreover, the phenomenon is also observed under helium atmosphere, which discards a possible role played by oxygen gas production and absorption.…”
Section: Iii3 Origin Of the Memory Effectscontrasting
confidence: 99%
See 3 more Smart Citations
“…In this case, ions are not accumulated and there is no building up of charge at the interface. This is in contradiction to what is observed in the present system where ions remain accumulated, a giant polarization (of the order of 0.1 C cm −2 ) is created 14 , and where no particular gas production is observed at the anode. Moreover, the phenomenon is also observed under helium atmosphere, which discards a possible role played by oxygen gas production and absorption.…”
Section: Iii3 Origin Of the Memory Effectscontrasting
confidence: 99%
“…Because of the diffusion force coming from the ionic concentration gradient, the ions motion is getting slower and slower. This regime is nothing but the appearance of the Warburg diffusion 23,24 , caused by the ionic accumulation and already observed in the low-frequency behavior of the dielectric constant 14 . Before the mobile ions begin to feel the edges of the sample they are in a free motion regime with a conductivity of 10 −4 S cm −1 related to the ionic conductivity 14 .…”
Section: Iv4 Discussion Of the Modelmentioning
confidence: 69%
See 2 more Smart Citations
“…Probably, V O ′′ will be associated with a cation vacancy forming (V Ti ′′′′ + 2V O ′′) complex, namely, the Shottky defect. Federicci et al in [177] reported a superionic conductor with a colossal dielectric constant for Rb 2 Ti 2 O 5 materials annealed under an oxygen-depleted atmosphere (such as He, N 2 , vacuum). They found that oxygen vacancies are created in the material, and the dielectric constant reaches the unprecedented value of 10 9 .…”
Section: Srtio3-based Biphase Ceramicsmentioning
confidence: 99%